2021
DOI: 10.2334/josnusd.20-0034
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extended polymerization time for different resin composites on reactive oxygen species production and cell viability

Abstract: Purpose: The present study was conducted to determine oxidative stress and cell viability after contact with resin composites polymerized for different times. Methods: Disk-shaped specimens of Admira Fusion, Ceram X One Universal, Solare x and Filtek Z550 (n = 12) were prepared, and two subgroups with polymerization times of 20 and 40 s were employed. The specimens were incubated with mouse fibroblast cells for 48 and 72 h, and changes in reactive oxygen species (ROS) production and cellular viability were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The degree of conversion after polymerization, the release of free monomers, and the degradation of the resin matrix causes various degrees of cytotoxicity. 10 Most of the composite resins available on the market used in treatments are not antibacterial because they contain inert inorganic fillers and organic monomers. Studies have reported that residual monomers released from composite resins may promote the growth and proliferation of microorganisms with the potential to cause caries.…”
Section: Biocompatibility Of Resin-containing Restorative Materialsmentioning
confidence: 99%
“…The degree of conversion after polymerization, the release of free monomers, and the degradation of the resin matrix causes various degrees of cytotoxicity. 10 Most of the composite resins available on the market used in treatments are not antibacterial because they contain inert inorganic fillers and organic monomers. Studies have reported that residual monomers released from composite resins may promote the growth and proliferation of microorganisms with the potential to cause caries.…”
Section: Biocompatibility Of Resin-containing Restorative Materialsmentioning
confidence: 99%